Les dilemmes de l’éthique au cœur des pratiques de différenciation - Andreea Capitanescu Benetti; Cynthia D’Addona; Lionel Dechamboux (Éducation et Socialisation)
Following the inclusion policy, primary school teachers of Geneva take into account pupils diversity by providing educational experiences and learning situations as constructive as possible. The aim of this research is to understand professional judgement for differentiating instruction as well as the values underlying it in the ordinary teaching practice. It is a qualitative research inductive by «grounded theory» based on comprehensive, semi-structured interviews on the declared practices of differentiation of ten teachers. Through an analysis of the content, regularities and variations of teaching practice, we find that professionals face dilemmas of differentiation complexity. Nevertheless, they pursuit to balance between several elements into their teacher practice or specific professional acts: a. compose with institutional prescriptions; b. to do with the class composition; c. the articulation of simultaneous teaching or tailor-made intervention; d. take care of the needs of each pupil and the needs of belonging to a collective, e. balance between support and devolution; f. make a balanced choice between equality and equity.